Spatial signatures of anesthesia-induced burst-suppression differ between primates and rodents - Sirmpilatze, Nikoloz; Mylius, Judith; Ortiz-Rios, Michael; Baudewig, Jürgen; Paasonen, Jaakko; Golkowski, Daniel; Ranft, Andreas; Ilg, Rüdiger; Gröhn, Olli; Boretius, Susann (eLife, 2022)
During deep anesthesia, the electroencephalographic (EEG) signal of the brain alternates between bursts of activity and periods of relative silence (suppressions). The origin of burst-suppression and its distribution across the brain remain matters of debate. In this work, we used functional magnetic resonance imaging (fMRI) to map the brain areas involved in anesthesia-induced burst-suppression across four mammalian species: humans, long-tailed macaques, common marmosets, and rats. At first, we determined the fMRI signatures of burst-suppression in human EEG-fMRI data. Applying this method to animal fMRI datasets, we found distinct burst-suppression signatures in all species. The burst-suppression maps revealed a marked inter-species difference: in rats, the entire neocortex engaged in burst-suppression, while in primates most sensory areas were excluded—predominantly the primary visual cortex. We anticipate that the identified species-specific fMRI signatures and whole-brain maps will guide future targeted studies investigating the cellular and molecular mechanisms of burst-suppression in unconscious states.
Gesehen am 08.07.2022